Entrepreneurship : principles and practices (a modular approach) - Azarcon, Ernie Roy S.; Areola, Adelberto;Arguelles, Roberto;Pablo-Barlis, Ma. Joan;Dela Pena, Glory;Drequito, Glory;Hocson, Leilani;Ireneo, Dorothy G. ;Lorilla-Lamadrid, Richel;Macasieb, April;Mendoza, Teresita;Nazario, Asuncion G.;Ngaosi, Lorraine B.;Pidal, Roberto (Baguio City : Valencia Educational Supply, 2005)
It is a book primarily designed to answer the challenge of presenting the course Entrepreneurship in a book matches the contents of the basic syllabi of the course.
MODULE 1. Entrepreneurship and the economy -- 2. The Entrepreneur -- 3. Basic Skills of an entrepreneur: ideation, Creativity and Innovation -- 4. Routes to entrepreneurship -- 5. Some small & medium enterprise programs & laws in the Philippines -- 6. Departments, Agencies & Bureaus involved in assisting small & medium Enterprise development -- 7. Legal forms and characteristics of business organizations -- 8. General requirements in putting up a business -- 9. Environmental scanning & Business opportunity identification -- 10. the Business plan -- 11. Fundamentals of Marketing -- 12. Production Planning & Layout -- 13. Organization & Management -- 14. Basic Business economics -- 15. Basic Finance.
Keywords: ENTREPRENEURSHIP